Comparison of digito-palmar dermatoglyphic traits in children with cerebral palsy and their close family members - Polovina Prološčić, Tajana (Array, 2009)
Abstract: Cerebral palsy is one of the main causes of severe disability in children. Sixty children (30 boys and 30 girls) were included in the study. Quantitative digito-palmar dermatoglyphic traits were analyzed. Prints of digito-palmar dermatoglyphs obtained from the children’s parents (60 mothers and 60 fathers) and from 400 phenotypically healthy adults from the Zagreb ware used as control groups. Analysis of quantitative dermatoglyphic traits of the digito-palmar complex revealed statistically significant differences in a number of variables between the fathers and their children suffering from cerebral palsy (TRC 180.3>158.6), with a greater number of variables involved in male children with cerebral palsy. Some variables showed statistically significant differences in dermatoglyphic patterns between fathers and control group of healthy males as well as between boys with cerebral palsy and healthy control males. Differences in dermatoglyphic patterns were significantly lower between mothers and girls with cerebral palsy (TRC 152.1<152.3) as well as between mothers and healthy control females. Study results support the hypothesis on the possible role of genetic predisposition in the occurrence of central nervous system lesion, with a more pronounced paternal impact